(untitled) (Nepal Journal of Epidemiology, 2021)
Background: Timely identification of adolescents with undernutrition is of utmost importance, and recently, mid-upper circumference (MUAC) had been considered as an alternative to body mass index (BMI) and BMI for age z-score (BAZ) for its screening. However, little is known about the MUAC cut-offs, specific to age and sex. The study was planned to assess the discriminatory performance of MUAC in identifying thin and severely thin adolescents and estimating age specific MUAC cut-offs, separately for males and females, against BAZ as the gold standard. Methods: The Comprehensive National Nutrition Survey (CNNS), India data was used for this analysis. The Receiver Operating Characteristic curve (ROC), area under curve (AUC), and Youden Index were used to estimate MUAC cut-off values for thin (BAZ < -2) and severely thin (BAZ < -3) adolescents. The current analysis was done on 31471 adolescents. Results: The MUAC cut-offs for identifying thin adolescents were: for 10-14 years – 19.2/19.4 cm, for 15-19 years – 22.9/21.7 cm for males and females respectively; and for severe thinness were: for 10-14 years – 18.4/18.3 cm, for 15-19 years – 21.9/20.2 cm for males/females. For thinness, the cut-off varied between 17.4-24.5 cm (for 10-19 years) among males, and for females, it varied between 17.5 -20.9 cm (for 10-19 years). For severe thinness, MUAC cut-off ranged between 16.4-23.7 cm (for 10-19 years) among males, and for females, between 17.3-20.7 cm (for 10-19 years). Conclusion: Thus, age- and sex-specific cut-offs could be considered for screening thin and severely thin adolescents.